Comparison between Sound Pressure Levels and Perception: a Soundscape Application in a University Campus. (September 2020) - Mascolo, A; Mancini, S; Graziuso, G; Quartieri, J; Guarnaccia, C
Abstract: The assessment and control of acoustic noise in every place in which humans live is usually performed measuring the sound pressure levels and comparing these results with the thresholds defined by regulations. The latest approaches include the possibility to consider the subjective perception of sounds, using the so-called "soundscape" approach. In this paper the authors present a practical application of this approach performed in the Campus of Fisciano, University of Salerno (Italy), with the aim to compare the physical parameters, obtained by measuring the sound level, and the psychoacoustics one, acquired by administering questionnaires to a group of students during a soundwalk. Results will show that the higher sound pressure levels will not always correspond to the more annoying places. In particular, the main park of the University campus will present a positive soundscape, even though noise from the nearby highway will be highly present. Similar conditions will occur in vibrant areas of the campus, in which the interviews will highlight a good perception of the soundscape, even with quite high sound pressure levels.